Penggunaan Project Based Learning dalam Meningkatkan Kreativitas dan Berpikir Kritis Peserta Didik pada Materi Bioteknologi - Nazwari, Aura; Agnes, Jistisya Maria; Pangaribuan, Selfiana; Anwar, Syakila; Khalisyah, Zhafira; Mukra, Rizal; Arwita, Widya (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
This study aims to analyze the use of the Project Based Learning (PjBL) model in improving students' creativity and critical thinking skills in biotechnology. This study uses a literature review method by examining various scientific articles published between 2020 and 2025 through Google Scholar. The data were analyzed using content analysis to examine previous research results related to the application of PjBL in biology learning. The results of the study indicate that the consistent application of PjBL has a positive impact on improving students' creativity and critical thinking skills. Through direct involvement in project activities such as the creation of simple biotechnology products, students actively build knowledge, increase motivation, and gain a more meaningful understanding of concepts. PjBL is also in line with the learning needs of the 21st century, which emphasizes four key skills (critical thinking, creativity, collaboration, and communication). Therefore, it can be concluded that PjBL is an effective, contextual, and relevant learning model for developing students' creativity and critical thinking skills on the topic of biotechnology.